PENERAPAN DIVERSI SEBAGAI IMPLEMENTASI PEMENUHAN HAK ASASI ANAK YANG BERKONFLIK DENGAN HUKUM - Luh Sri Widi Artini; Putu Bagus Sabda Pramesti (Universitas Halu Oleo, 2020)
A child who commits a legal offence is a special concern from the state. Diversi is the application of versioning is an effort from the government to protect the child from negative stigmatization and based on the best needs and interests for children, by seeking a version through the approach of Restorative justice. This research aims to determine how the implementation is versioned as a child's human rights implementation and what constraints are faced by related parties in the running of versioning. This research uses a qualitative method of research approach with a literature study technique that is further analyzed qualitatively. Children are trusting and give that must be guarded because the child is the hope of the state as a nation's successor so that children should be protected. The results of this study show that versioning is one of the government's efforts to protect the child's rights from adverse influences and the stigmatization of the community and is done for the best interest of the child. Obstacles faced in the form of lack of the presence and the existence of a sectoral ego between the law enforcement officers so that the version has not run optimally and the need to socialize about the law of the Child criminal system Community.